2020
DOI: 10.1523/eneuro.0537-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Modulates Early Memory Consolidation in Humans

Abstract: Maintenance of memory across time is crucial for adaptive behavior. Current theories posit that the underlying consolidation process depends on stabilization of synapses and reorganization of interactions between hippocampus and neocortex. However, the temporal properties of hippocampal-neocortical network reconfiguration during consolidation are still a matter of debate. Translational research on this issue is challenged by the paucity of techniques to transiently interfere with memory in the healthy human br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is believed that ensemble formation is mediated in part by use-dependent synaptic plasticity, such as NMDA receptor (NMDAR)-dependent long-term potentiation (LTP), initiated by oscillatory brain activity (rhythms) and regulated by a variety of neuromodulators such as brain-derived neurotrophic factor (BDNF), dopamine, and acetylcholine (ACh). These oscillations effectively enable both the formation and consolidation of memories through repeated circuit activation in the days and nights following learning events (Norimoto et al, 2018 ; Malerba and Bazhenov, 2019 ; Eichenlaub et al, 2020 ; Moon et al, 2020 ; Nguyen et al, 2020 ; Patel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that ensemble formation is mediated in part by use-dependent synaptic plasticity, such as NMDA receptor (NMDAR)-dependent long-term potentiation (LTP), initiated by oscillatory brain activity (rhythms) and regulated by a variety of neuromodulators such as brain-derived neurotrophic factor (BDNF), dopamine, and acetylcholine (ACh). These oscillations effectively enable both the formation and consolidation of memories through repeated circuit activation in the days and nights following learning events (Norimoto et al, 2018 ; Malerba and Bazhenov, 2019 ; Eichenlaub et al, 2020 ; Moon et al, 2020 ; Nguyen et al, 2020 ; Patel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is widely used during invasive diagnostic and surgical procedures and for sedation, including in newborns and young children. 1,4,[6][7][8] Compared to other intravenous anesthetics, propofol-induced anesthesia is associated with fewer side effects and faster recovery. The benefits of propofol include the rapid onset of anesthesia and short recovery time, 4 as well as neuroprotective effects in pathogenic situations.…”
Section: Introductionmentioning
confidence: 99%
“…After encoding, synaptic consolidation is thought to occur within seconds to hours while systems consolidation may continue for months or even years (Kelleher et al, 2004;Smith and Squire, 2009;Takashima et al, 2009). Recently, the traditional view on memory consolidation has been challenged by research suggesting that significant hippocampal-neocortical rearrangement can occur within minutes after encoding (Lesburguères et al, 2011;Kitamura et al, 2017;Moon et al, 2020;Tambini and D'Esposito, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A potential pharmacological approach is the shortacting anaesthetic propofol (2,6-diisopropylphenol), which is commonly used in routine medical procedures (Sahinovic et al, 2018;Walsh, 2018). Propofol acts as an agonist on the g-aminobutyric-acid (GABA)-A-receptor and as a partial antagonist on (NMDA)-receptors, affecting long-term-potentiation and synaptic consolidation in hippocampal slices as well as hippocampus-dependent memory consolidation (Wei et al, 2002;Nagashima et al, 2005;Zhang et al, 2013;Moon et al, 2020). An fMRI study showed that even sub-hypnotic doses of propofol are sufficient to modulate hippocampal activity in humans (Pryor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation